Develop and test a micropump based on acoustic impedance mismatch - Muhammad Syafiq Sedek (Nanyang Technological University, 2021)
The concept of impedance pumping and the reasonings behind its mechanism have long been studied over the years and many findings have emerged from the extensive research. This Final Year Project (FYP) report aims to expound further the said concept and investigate and analyse the effect of acoustic impedance mismatch that allows for impedance pumping to take place. By carrying out experiments using two-closed loop system models and introducing parameters for comparison, this project will analyse the changes in fluid flow rate and the direction of flow of the fluid observed within the system because of factors like actuator position, frequency, current output, and size of indicator used to track the flow rate and its direction. The pumping mechanism involves the Liebau effect which takes place when fluid is contained within tubes made of materials of different relative impedances and compressions are made on asymmetric points on the material with flexible properties, and this generates fluid flow. The compressions are provided by the compression beam which acts as an actuator. The objective of this project is to investigate whether the findings from the experiments in this FYP resembles the findings from open literatures and past experiments. Thus, conclusions will be drawn based on the observations made and the data collected to deduce whether the findings are similar to the previous experiments conducted and they will be further detailed in the Conclusions and Recommendations chapter.